No patella resurfacing total knee arthroplasty leads to reduction in the thickness of patellar cartilage to less than half within 5 years: a quantitative longitudinal evaluation using MRI - Dai Sato (SpringerOpen, 2021)
Abstract Purpose Patellar resurfacing in total knee arthroplasty (TKA) remains controversial as recent meta-analyses have not shown its clear superiority; however, most authors recommend it because it is associated with less frequent anterior knee pain and need for reoperation. We aimed to clarify the changes in patellar cartilage thickness in no patellar resurfacing TKA using a ceramic femoral component on magnetic resonance imaging (MRI). Methods Between 2009 and 2014, 40 consecutive patients (59 knees) were included in this study. All patients underwent TKA using zirconia ceramic femoral implants without patellar resurfacing. Indications for no patellar resurfacing TKA were absence of anterior knee pain, patellar compression pain, and osteoarthritic changes in the patellofemoral joint on plain radiography. The mean postoperative follow-up duration was 81.5 months (range, 25–131 months). Clinical and radiological evaluations were performed preoperatively and 5 years after TKA. Patellar cartilage thickness was evaluated preoperatively and every year for 5 years after TKA using MRI T2-weighted imaging. The patellar cartilage was divided into three regions of interest: medial, central, and lateral. To standardise the variation in patellar thickness among patients, the percent cartilage thickness was calculated. Results The implant’s position was appropriate in all cases. Compared to preoperative scores, 5 years postoperatively, the Japanese Orthopedic Association score and Oxford knee score significantly improved from 52.1 to 84.7; mean tilting angle and congruence angle did not change significantly; mean lateral shift ratio significantly increased from 7.1% to 14.6%; cartilage thickness significantly decreased (P < 0.05); and the percentage cartilage thickness of the central, medial, and lateral cartilage zones gradually thinned to less than half. Four patients underwent conversion to patellar resurfacing due to anterior knee pain, without loosening the femoral and tibial implants. Conclusion The patellar cartilage thickness decreased to less than half its preoperative level within 5 years after no patellar resurfacing TKA; this would led to clinical problems and conversion to patellar resurfacing. Level of evidence Level III.